Long-term performance of permeable reactive barriers. - Roehl, K. E. (Karl Ernst) (Trace metals in the environment, 2005)
"Permeable Reactive Barriers (PRBs) use an innovative, in-situ technology for the remedial treatment of contaminated groundwater. The book describes methods for the evaluation and enhancement of long-term performance of PRBs, which is the decisive factor in determining their economic viability. Treating uranium contaminated groundwater, a legacy of uranium mining, is the central theme of the book. Suitable reactive materials for use in PRBs are identified, attenuation processes are characterised, new contaminant-binding chemical compounds are developed, accelerated testing methods are used to assess the long-term performance, electokinetic techniques to enhance efficiency are discussed, and the results of monitoring existing and new field installations are reported. These themes are developed around two case studies, one at the site of the former Hungarian uranium ore mining and processing near the city of Pecs in Hungary and one at a former industrial site in Brunn am Gebirge in Austria, where an activated carbon PRB system is being used to treat a plume of organic contaminants."--Jacket